Fostering farmers’ innovativeness through training and extension approaches: A systematic literature review - Nouatin, Farêne G.K.; Gouroubera, Mori W.; Moumouni-Moussa, Ismail (Elsevier, 2025)
Despite the recognized importance of agricultural extension approaches and farmers' innovation in addressing challenges within the agrifood sector, the existing literature on how these extension approaches influence farmers' innovativeness remains fragmented. This fragmentation provides limited guidance for policymakers and practitioners, hindering effective decision-making and the development of best practices. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the review analyzed 33 empirical studies focused on enhancing farmers' innovativeness in Africa. This analysis was based on a search that yielded 2891 records published up to June 29, 2024. These records were meticulously screened to meet predefined inclusion criteria. The studies were sourced from the Web of Science and Scopus databases, with additional documents identified through Google Scholar. The findings reveal that (1) farmers' innovativeness varies across different extension approaches; (2) digital-based approaches promote the highest levels of innovation adoption, mainly for non-technological innovation, while integrated approaches perform best for technological innovations; (3) both digital-based and integrated approaches are more effective for knowledge acquisition; (4) digital-based and multi-stakeholder approaches are more effective for fostering continuous innovation; (5) capacity building, community and social networks, and access to resources and support emerged as the most significant drivers of farmers’ innovativeness; and (6) positive impacts with a greater focus on environmental and economic dimensions were reported, although variability in outcomes suggests that context-specific factors play a crucial role. This review provides valuable insights for policymakers and practitioners aiming to improve agricultural extension services and foster farmers' innovativeness. It emphasizes the need for context-sensitive approaches that support farmers in navigating complex agricultural challenges.